Development of Learning Tools by Application of Problem Based Learning Models to Improve Mathematical Communication Capabilities of Sequence and Series Materials - Atika, Nur; Roza, Yenita; Murni, Atma (FKIP-Universitas Riau, 2020)
This research was motivated by the lack of learning tools that can improve students' Mathematical Communication Skills (KKM). Activities that can encourage students to improve KKM have not been designed by the teacher in the learning device properly. This study aims to produce learning tools by applying Problem Based Learning models to improve KKM. This development research used the ADDIE development model with the stages of Analysis, Design, Development, Implementation, and Evaluation. The results of Syllabus, RPP, LKPD and KKM validation results showed highly valid criteria with percentages of91.67%, 91.30%, 89.09%, and 87.15%, respectively.Practicality results indicate a very practical criterion with the percentage of small group trials at 95.57%, large group trials at 96.07%, and teacher responses at 96.25%. The effectiveness test results state that KKM of students who use learning tools with PBL models is better than KKM of students who use conventional learning.